A study of maternal and fetal outcomes in critically ill obstetric patients - Tasneem, Fasiha; Sharma, Vinutha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy related morbidity is becoming a nightmare in Indian women. Some of these women end up in mortality and a few of them narrowly escape death. Critical care should be and is an authenticated part of obstetric practice. This study is an effort initiated to understand the risk of maternal morbidity, to investigate the contributing factors, foetal outcome, to study the adverse event, cause of maternal death and remedial measures. Methods: All the obstetric cases admitted in Intensive care unit in a government institute in Maharashtra during January 2018 to June 2019 were analyzed prospectively. The indications for transfer into intensive care, risk factors, co morbidities if any were studied. Maternal and fetal morbidity and mortality were included in the study. Results: During the study period, there were 10, 208 deliveries. There were 12 maternal deaths and 98 critically ill patients became morbid. Anemia is found to be a major pre-existing contributing factor (25.5%) and an important risk factor making pregnancy become critical. DIC is found to be a major reason for ICU admission (39.1%), 72.7% needed mechanical ventilator and 60.1% needed ionotropic support. Conclusions: Anemia is a major problem still existing in our country. Gestational hypertension is another leading cause of critical illness in pregnancy. Identification of patients who are going downhill, timely referral to higher centers and appropriate management can improve both the maternal and the fetal outcomes.